1978
DOI: 10.1530/acta.0.0890393
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and in Vivo Studies on Leydig Cell Function in Old Rats

Abstract: Young adult (3 months old) and old (26\p=n-\28 months old) male Wistar rats were studied. Testicular weight was 1.66 g (range: 1.33 \p=n-\ 2.86) in the younger group and 1.62 g (range: 1.04 \p=n-\ 1.90) in the older group. The total Leydig cell volume as measured by a quantitative histometric method was significantly larger in the old animals (\l =x_\ = 0.153 ml vs. \l=x_\ = 0.089 ml). The testicular HCG binding capacity was 2.54 ng HCG per 100 mg tissue (range: 1.88 \p=n-\3.77) in the younger animals and 1.83… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
1

Year Published

1983
1983
2013
2013

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 8 publications
0
18
1
Order By: Relevance
“…Tsitouras et al, [184] reported that in vivo pretreatment with, but not in vitro exposure to, hCG reverses the testosterone secretory defect of Leydig cells from old rats. Overall, these changes appear not to be a function of gonadotropin receptor activity, or cAMP formation [162,177,182,183,185,186] or a defect in the steroid hormone synthesizing enzymes [176,186] although there are some exceptions to this. For example, Pirke et al, [162] reported significant loss of hCG binding to whole testicular membranes of old rats, while Tsitouras et al, [182] observed only a modest decrease in hCG binding to membrane preparations from the purified Leydig cells.…”
Section: Experimental Animalsmentioning
confidence: 93%
See 4 more Smart Citations
“…Tsitouras et al, [184] reported that in vivo pretreatment with, but not in vitro exposure to, hCG reverses the testosterone secretory defect of Leydig cells from old rats. Overall, these changes appear not to be a function of gonadotropin receptor activity, or cAMP formation [162,177,182,183,185,186] or a defect in the steroid hormone synthesizing enzymes [176,186] although there are some exceptions to this. For example, Pirke et al, [162] reported significant loss of hCG binding to whole testicular membranes of old rats, while Tsitouras et al, [182] observed only a modest decrease in hCG binding to membrane preparations from the purified Leydig cells.…”
Section: Experimental Animalsmentioning
confidence: 93%
“…Likewise, aged Leydig cells from Brown Norway rats also exhibited a significant reduction in gonadotropin (LH) receptor content [187]. Contrary to these findings, other investigators failed to observe any reduction in gonadotropin binding either in vivo [162] or in vitro [177,185,188]. In addition, gonadotropin stimulation of cAMP production and PKA activity in Leydig cells was unaffected by the aging process [182,183,186].…”
Section: Experimental Animalsmentioning
confidence: 95%
See 3 more Smart Citations